DYNAMICS OF MICROBIOLOGICAL AND OXIDATIVE STABILITY OF WHITE WINES DURING THE TECHNOLOGICAL PROCESS - NATALIA VLADEI; VALERIA DAMASCHIN; ECATERINA COVACI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Oxidation and the capacity for sufficient aging potential of white wines are constant problems for winemakers worldwide. The article analyses the correlation between the microbiological and oxidative stability of white wines and the main redox processes occurring in the technological stages of the wines. In micro-winery TUM conditions, parallel and spontaneous development of several redox processes and their impact on the quality, microbiological and oxidative stability of white wines were examined. As a result, the developed technological scheme has managed to provide a solution that is effective in properly controlling the oxidation process and preserving the white wine quality.